Generation of Intense Phase-Stable Femtosecond Hard X-ray Pulse Pairs - Zhang, Yu; Kroll, Thomas; Weninger, Clemens; Michine, Yurina; Fuller, Franklin D; Zhu, Diling; Alonso-Mori, Roberto; Sokaras, Dimosthenis; Lutman, Alberto; Halavanau, Aliaksei; Pellegrini, Claudio; Benediktovitch, Andrei; et al. (arXiv.org, 2021)
Coherent nonlinear spectroscopies and imaging in the X-ray domain provide direct insight into the coupled motions of electrons and nuclei with resolution on the electronic length and time scale. The experimental realization of such techniques will strongly benefit from access to intense, coherent pairs of femtosecond X-ray pulses. We have observed phase-stable X-ray pulse pairs containing more thank 3 x 10e7 photons at 5.9 keV (2.1 Angstrom) with about 1 fs duration and 2-5 fs separation. The highly directional pulse pairs are manifested by interference fringes in the superfluorescent and seeded stimulated manganese K-alpha emission induced by an X-ray free-electron laser. The fringes constitute the time-frequency X-ray analogue of the Young double-slit interference allowing for frequency-domain X-ray measurements with attosecond time resolution.